THE EFFECT OF PRODUCTION AND MARKETING ASSISTANCE ON THE DEVELOPMENT OF MICRO, SMALL AND MEDIUM ENTERPRISES - Suwarso - (MBA - Journal of Management and Business Aplication, 2022)
One of the functions of higher education is as a medium for transferring knowledge to thecommunity, namely research and community service. Through this program, the authorconducted a research entitled the effect of production and marketing assistance on thedevelopment of micro, small and medium enterprises at UD. Seger Prosperous BanyuwangiRegency. The method used in this research is direct observation to the field. The results of thisstudy, that the influence of production and marketing assistance on the development of micro,small and medium enterprises (UD. Seger Makmur Banyuwangi Regency), there is a significantincrease in the quantity and quality of production with equipment innovation. Meanwhile, interms of marketing, with the planned promotion there is a significant increase in the quantity ofnew customers, wider market coverage and increased revenue.Keywords: Assitance, production, marketing.